Exogenous and intention-dependent control of attention shifts in dynamic displays - Scharlau, Ingrid; Ansorge, Ulrich (Dynamic Perception: Workshop of GI section 1.0.4 "Image Understanding" and the European Networks MUHCI and ECOVISION)

Leading, but not trailing, primes influence temporal order perception: Further evidence for an attentional account of perceptual latency priming. - Scharlau, Ingrid (Perception & Psychophysics)
Presenting a masked prime leading a target influences the perceived onset of the masking target. This priming effect is explained by the asynchronous updating model: The prime initiates attentional allocation toward its location, which renders a trailing target at the same place consciously available earlier. In 3 experiments, this perceptual latency priming by leading primes was examined jointly with the effects of trailing primes in order to compare the explanation of the asynchronous updating model with the onset-averaging and the P-center hypotheses. Exp 1 (n=15, mean age 27.1 yrs) showed that an attended, as well as an unattended, prime leads to perceptual latency priming. In addition, a large effect of trailing primes on the onset of a target was found. As Exp 2 (n=13, mean age 26.5 yrs) demonstrated, this effect is quite robust, although smaller than that of a leading prime. In Exp 3 (n=13, mean age 24.8 yrs), masked primes were used. Under these conditions, no influence of tra
Keywords: attention; leading primes; trailing primes; temporal order perception; perceptual latency priming; Adult; Attention; Female; Fixation; Ocular; Humans; Male; Perceptual Masking; Random Allocation; Time Perception; Visual Perception; Attention; Masking; Priming; Stimulus Frequency; Temporal Frequency; Temporal Order (Judgment)

Familien mit Kindern im frühen Erwachsenenalter - Papastefanou, Christiane; Buhl, Heike M. (Lehrbuch Familienbeziehungen. Eltern und Kinder in der Entwicklung)

Ideenzirkulation und Zirkulation von Ideen. Zur empirischen Psychologie der Berliner Spätaufklärung (am Beispiel Marcus Herz) - Steigerwald, Jörn (Gedächtnis und Zirkulation. Der Diskurs des Kreislaufs im 18. und frühen 19. Jahrhunderts)

"Der Kampf ist nicht nur eine Vernichtung, sondern auch die männliche Form der Zeugung." Ernst Jünger und das "radikale Geschlecht" des Kriegers - Öhlschläger, Claudia (Kunst-Zeugung-Geburt. Theorien und Metaphern ästhetischer Produktion in der Neuzeit)

Weiße Räume. Transgressionserfahrungen bei Adalbert Stifter - Öhlschläger, Claudia (Jahrbuch des Adalbert-Stifter-Institutes des Landes Oberösterreich. (2002/2003) Erscheinungsjahr 2005)

Phantasia in Utero. Weibliche Imagination im anthropologischen Diskurs der französischen Aufklärung - Steigerwald, Jörn (Imagination – Fiktion – Kreation: Das kulturschaffende Vermögen der Phantasie)

Der männliche Blick auf die weibliche Imagination - Steigerwald, Jörn (Rubin. Wissenschaftsmagazin der Ruhr-Universität Bochum. 12, 2002)

Solitons and production of defects in flow-aligning nematic liquid crystals under simple shear flow - Yang, Yuliang; Luo, K. F.; Schmidt, Claudia; Peter, Christine (Progress in Natural Science)
The production of defects in flow-aligning nematic liquid crystals under simple shear flow is analyzed by linear stability analysis based on Leslie-Ericksen theory. It is pointed out that the equation of motion of the nematic director under simple shear flow conforms to the driven over-damped sine-Gordon equation and has a soliton solution of amplitude pi. It has also been shown that the stationary state with the director uniformly oriented at a Leslie angle is only a metastable state and that the potential, which governs the motion of the director, has infinite numbers of stable stationary states. Therefore, the defects, appearing as a stable solitary solution, can be nucleated from a uniformly aligned flow-aligning type of nematic liquid crystal by shear flow. On the other hand, the bands with long axis parallel to the vorticity axis, appearing as an unstable-solution, can be observed as transient patterns at tow shear rate and low shear strain value, The theoretical predictions are compared with previous experimental observations.
Keywords: nematic liquid crystalsdefectssolitons

Evaluation of the viscoelastic properties of a nematic dimer by cone-and-plate rheo-nuclear magnetic resonance spectroscopy and comparison with Leslie–Ericksen theory - Lukaschek, Michail; Kothe, Gerd; Schmidt, Claudia; Gomes, Alexandre E.; Polimeno, Antonino (The Journal of Chemical Physics)
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Lyotropic Mesophases Next to Highly Efficient Microemulsions: A 2H NMR Study - Stubenrauch, Cosima; Frank, Christian; Strey, Reinhard; Burgemeister, Daniel; Schmidt, Claudia (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

In Situ Deuteron NMR Investigations of Sheared Liquid Crystalline Polymers - Siebert, Hartmut; Becker, Patrick; Quijada-Garrido, Isabel; Grabowski, David A.; Schmidt, Claudia (Solid State Nuclear Magnetic Resonance)
Keywords: Instrumentation; Nuclear and High Energy Physics; General Chemistry; Radiation

Schrifterwerbskonzepte zwischen Sprachwissenschaft und Pädagogik

Sprache als Form. FS für Utz Maas

Die Schärfungsschreibung im Fokus. Zur schriftlichen Repräsentation sprachlicher Strukturen im Spannungsfeld von Sprachwissenschaft und Didaktik

Texttypologie aus diachroner Sicht - Tophinke, Doris (Textsorten im romanischen Sprachvergleich)

Lebensgeschichte und Sprache. Zum Konzept der Sprachbiografie aus linguistischer Sicht - Tophinke, Doris (Bulletin suisse de linguistique appliquée)

Die lautlich-segmentale Analyse des Gesprochenen und ihre Forcierung im Schrifterwerb - Tophinke, Doris (Schrifterwerbskonzepte zwischen Sprachwissenschaft und Pädagogik)

Plädoyer für eine kontextsensitive Modellierung von Spracheinstellungen - Tophinke, Doris; Ziegler, Evelyn (Zeitenwende – Die Germanistik auf dem Weg vom 20. ins 21. Jahrhundert. Akten des X. Internationalen Germanistenkongresses Wien 2000. Bd. 3)

Schreiben gegen die Regel – Formen und Funktionen orthografischer Abweichungen im Internet Relay Chat (IRC) - Tophinke, Doris (Sprache als Form. FS für Utz Maas)

Computing sums of radicals in polynomial time - Blömer, Johannes ([1991] Proceedings 32nd Annual Symposium of Foundations of Computer Science)

Denesting by Bounded Degree Radicals - Blömer, J. (Algorithmica)
Keywords: Applied Mathematics; Computer Science Applications; General Computer Science

Gute Gründe für eine Ontologie der Ökonomie und der Unternehmung auf Basis der Basic Formal Ontology (BFO) - Hagengruber, Ruth Edith (Towards a Basal Enterprise Ontology, Eco-Reports. Arbeitsberichte des Fachbereichs Wirtschaftsinformatik, Forschungsgruppe Unternehmensmodellierung, Bereich Wissenschaftstheorie)

Towards a Basal Enterprise Ontology, Eco-Reports. Arbeitsberichte des Fachbereichs Wirtschaftsinformatik, Forschungsgruppe Unternehmensmodellierung, Bereich Wissenschaftstheorie

Vernunftkritik und biophile Begrifflichkeit. Französische Philosophie im 20. Jahrhundert - Hagengruber, Ruth Edith (Das Denken des Anderen)

Ein streitbares Ding - Hagengruber, Ruth Edith (Dinge – Medien der Aneignung - Grenzen der Verfügung)

Was es heißt, rational zu handeln. Bemerkungen zum ökonomischen und kreativen Rationalitätsverständnis - Hagengruber, Ruth Edith (Knowledge – Gender – Power/ Wissen – Macht – Geschlecht)

Gegen Rousseau - für die Physik. Gabrielle Emilie Du Châtelet (1706-1749). Das Leben einer Wissenschaftlerin im Zeitalter der Aufklärung - Hagengruber, Ruth Edith (Konsens)

Cyberfeminism Crossover: Talking about Intercultural and Interdisciplinary Experience - Weber, Jutta (Feminist Challenges in the Information Age. Information as a Social Resource)

Technoscience als Epoche? Ontologische, epistemologische und narrative Grundlagen der Techno/Wissenschaften - Weber, Jutta (Techniken der Reproduktion: Medien, Leben, Diskurse)

Kulturelle und Geschlechterperspektiven auf die Informatik - Weber, Jutta; Bath, Corinna (Wozu Informatik? Theorie zwischen Ideologie, Utopie, Phantasie. Materialien zu einer Arbeitstagung in Bad Hersfeld März 2002. Bericht 2002 – 25 der Fakultät IV – Elektrotechnik und Informatik)

Mathematics of Life. Constitution of A New Concept of Life Through Artificial Life Research - Weber, Jutta; Ebeling, Smilla (Proceedings of the 5th German Workshop on Artificial Life. Abstracting and Synthesizing the Principles of Living Systems)

TechnoTricksterTank™4Today - Weber, Jutta; Bath, Corinna; Peter, Uli; Draude, Claude; Gössler, Alice (very cyberfeminist international. obn conference, hamburg, december 13-16, 2001)

Berechenbare Organismen, wildgewordene Maschinen? Heilsvisionen und Apocalyptica der Artificial-Life-Forschung - Weber, Jutta (Cyberfeminismus. Feministische Visionen mit Netz und ohne Boden. In: Bulletin Nr. 24. Texte)

Darstellung und Bewertung von Online und Offline Medien unter dem Gesichtspunkt nachhaltiger Ernährungsstile. Lehren und Lernen im haushaltsbezogenen Unterricht. - Bigga, Regine; Schack, Pirjo Susanne (Haushalt & Bildung)

(K)ein Land in Sicht? Eine Kritik des Wissenschaftsjournalismus im Sekundärmedium Internet - Schuster, Britt-Marie; Seyfferth, Henriette (www.germanistik2001.de. Vorträge und Referate des Erlanger Germanistentages)

Influence of iron–silicon interaction on the growth of carbon nanotubes produced by chemical vapor deposition - de los Arcos de Pedro, Maria Teresa; Vonau, F.; Garnier, M. G.; Thommen, V.; Boyen, H.-G.; Oelhafen, P.; Düggelin, M.; Mathis, D.; Guggenheim, R. (Applied Physics Letters)

Fast Processes in a N2O-Modulated Hollow Cathode Discharge: Excitation and Diffusion - de los Arcos de Pedro, Maria Teresa; Castillo, M.; Domingo, C.; Herrero, V. J.; Sanz, M. M.; Tanarro, I. (The Journal of Physical Chemistry A)

Gas phase FT-IR absorption spectroscopy as a quantitative diagnostic method for cold plasmas - Domingo, C; de los Arcos de Pedro, Maria Teresa; Ainetschian, A; Sanz, M.M; Tanarro, I (Vibrational Spectroscopy)

Diagnostics and modeling of glow discharges by time-resolved IR absorption spectroscopy - Tanarro, I.; de los Arcos de Pedro, Maria Teresa; Domingo, C.; Herrero, V.J.; Sanz, M.M. (Vacuum)

Preparation and characterization of TiN–Ag nanocomposite films - de los Arcos de Pedro, Maria Teresa; Oelhafen, P; Aebi, U; Hefti, A; Düggelin, M; Mathys, D; Guggenheim, R (Vacuum)

Diagnostics and Kinetic Modeling of the Ignition and the Extinction Transients of a Hollow Cathode N2O Discharge - de los Arcos de Pedro, Maria Teresa; Domingo, C.; Herrero, V. J.; Sanz, M. M.; Tanarro, I. (The Journal of Physical Chemistry A)

Diagnostics and Kinetic Modeling of a Hollow Cathode N2O Discharge - de los Arcos de Pedro, Maria Teresa; Domingo, C.; Herrero, V. J.; Sanz, M. M.; Schulz, A.; Tanarro, I. (The Journal of Physical Chemistry A)

RDL/TT - A Description Language for Profile-Dependent Transcoding of XML Documents - Schäfer, Robbie; Dangberg, Andreas; Müller, Wolfgang (Proceedings of the VHE Workshop)
With the increasing availability of various web-enabled mobile devices, content has to be effectively adapted to their different limitations. So, web content need rearrangement, i.e., a transcoding, to better fit on small displays when, for instance, layout specific HTML structures like tables and frames are used. In this article, we present a description language to define generic rules for this purpose and introduce RDL/TT (Rule Description Language for Tree Transformation). RDL/TT specifies sets of transcoding functions generic to user and hardware profiles. A Java-oriented syntax is used to describe the transcoding functions which operate on the DOM (Document Object Model) tree representation of an HTML or XML document.

Distributed Video-on-Demand Services on Peer to Peer Basis - Loeser, Chris; Altenbernd, Peter; Ditze, Michael; Müller, Wolfgang (Proceedings of the Intl. Workshop on Real-Time LANs in the Internet Age (RTLIA 2002))
Within this paper we propose architecture ideas of a distributed Video on Demand network which base on peer to peer technology. Each peer offers video streams to other peers and may receive a video stream from another peer simultaneously. This results in an optimization problem depending on different factors which we approximate with the help of an simulation environment. Our approach bases on a peer to peer framework by Sun called Project JXTA which provides a set of protocols for P2P applications.

Fuzzy Rules for the Transcoding of HTML Files - Schäfer, Robbie; Müller, Wolfgang; Dangberg, Andreas (Proceedings of the HICSS-35)

A UML Profile for Real-Time Constraints with the OCL - Flake, Stephan; Müller, Wolfgang (Proceedings of the UML 2002 - The Unified Modeling Language)
This article presents a UML profile for an OCL extension that enables modelers to specify behavioral, state-oriented real-time constraints in OCL. In order to perform a seamless integration into the upcoming UML2.0 standard, we take the latest OCL2.0 metamodel proposal by Warmer et al. [22] as a basis. A formal semantics of our temporal OCL extension is given by a mapping to time-annotated temporal logics formulae. To give an example of the applicability of our extension, we consider a modeling approach for manufacturing systems called MFERT. We present a corresponding UML profile for that approach and combine both profiles for formal verification by real-time model checking.

Graphische Spezifikation und Echtzeitverifikation von Produktionsautomatisierungssystemen - Dangelmeier, Wilhelm; Darnedde, C.; Flake, Stephan; Müller, Wolfgang; Pape, U.

Imaging of liquid crystals using a new scanning near-field optical microscope with microfabricated tips and shear force detection - Röder, Th.; Paelke, L.; Held, N.; Vinzelberg, S.; Kitzerow, Heinz-Siegfried (Review of Scientific Instruments)
Keywords: Instrumentation

Scanning near-field optical microscopy of cholesteric liquid crystals - Huser, Thomas; Lacoste, Thilo; Heinzelmann, Harry; Kitzerow, Heinz-Siegfried (The Journal of Chemical Physics)
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

“Ich, der ich an keine Wunder glaube, will ein Wunder, an das ich glaube, erzählen.” – Ich-Auflösung und die Struktur des Paradoxen in Friedrich Maximilian Klingers Drama Sturm und Drang - Morrien, Rita (Weimarer Beiträge)

Über die Kunst, ‘natürlich’ zu sein. Die weibliche Schönheit als Schauplatz der Naturalisierung der Geschlechterdifferenz in Romanen um 1800 - Morrien, Rita (Literatur für Leser)

Die schreckliche Schönheit des Vergangenen – Dimensionen historischen Erzählens in Stifters Der Hochwald und Storms Eekenhof - Morrien, Rita (Literatur für Leser)

Der dunkle “Garten der Vergangenheit” – historisches Erzählen als Lizenz zur Ausschweifung in den Chroniknovellen Theodor Storms. Festvortrag der Storm-Tagung 2001 - Morrien, Rita (Schriften der Theodor-Storm-Gesellschaft)

Fluorescent columnar liquid crystalline 3,4,9,10-tetra-(n-alkoxycarbonyl)-perylenes - Benning, S.; Kitzerow, Heinz-Siegfried; Bock, H.; Achard, M.-F. (Liquid Crystals)
Keywords: Condensed Matter Physics; General Materials Science; General Chemistry

Thermotropic Liquid Crystals from Planar Chiral Compounds: Optically Active Mesogenic [2.2]Paracyclophane Derivatives - Popova, Elena L.; Rozenberg, Valeria I.; Starikova, Zoya A.; Keuker-Baumann, Susanne; Kitzerow, Heinz-Siegfried; Hopf, Henning (Angewandte Chemie International Edition)
Keywords: General Chemistry; Catalysis

Absorption and luminescence spectra of electroluminescent liquid crystals with triphenylene, pyrene and perylene units - Keuker-Baumann, Susanne; Bock, Harald; Sala, Fabio Della; Benning, Stephan A.; Haßheider, Thomas; Frauenheim, Thomas; Kitzerow, Heinz-Siegfried (Liquid Crystals)
Keywords: Condensed Matter Physics; General Materials Science; General Chemistry

Standard (NRZ 1 x 40 Gb/s, 210 km) and polarization multiplex (CS-RZ, 2 x 40 Gb/s, 212 km) transmissions with PMD compensation - Sandel, D; Wust, F; Mirvoda, V; Noé, Reinhold (IEEE PHOTONICS TECHNOLOGY LETTERS)

Polarization mode dispersion detected by arrival time measurement of polarization-scrambled light - Noé, Reinhold; Sandel, D; Mirvoda, V; Wust, F; Hinz, S (JOURNAL OF LIGHTWAVE TECHNOLOGY)

Signed online chromatic dispersion detection at 40 Gbit/s based on arrival time detection with 60 attosecond dynamic accuracy - Sandel, D; Mirvoda, V; Wust, F; Noé, Reinhold; Weiske, CJ (ELECTRONICS LETTERS)

Linear detection of optical polarization mode dispersion by arrival time modulation - Mirvoda, V; Sandel, D; Wust, F; Hinz, S; Noé, Reinhold (ELECTRICAL ENGINEERING)

Standard (NRZ 1 x 40 Gb/s, 210 km) and polarization multiplex (CS-RZ, 2 x 40 Gb/s, 212 km) transmissions with PMD compensation - Sandel, D; Wust, F; Mirvoda, V; Noé, Reinhold (IEEE PHOTONICS TECHNOLOGY LETTERS)

Polarization mode dispersion detected by arrival time measurement of polarization-scrambled light - Noé, Reinhold; Sandel, D; Mirvoda, V; Wust, F; Hinz, S (JOURNAL OF LIGHTWAVE TECHNOLOGY)

Signed online chromatic dispersion detection at 40 Gbit/s based on arrival time detection with 60 attosecond dynamic accuracy - Sandel, D; Mirvoda, V; Wust, F; Noé, Reinhold; Weiske, CJ (ELECTRONICS LETTERS)

Höfische Liebe: Entwürfe der Sangspruchdichtung. Literarische Verfahrensweisen von Reinmar von Zweter bis Frauenlob - Egidi, Margreth

Construction of Quaternary Stereocenters by Nickel-Catalysis of Asymmetric Michael Reactions - Christoffers, Jens; Rößler, Ulrich; Werner, Thomas (European Journal of Organic Chemistry)
Keywords: Organic Chemistry; Physical and Theoretical Chemistry

Cerium-catalyzed α-Oxidation of β-Dicarbonyl Compounds with Molecular Oxygen - Christoffers, Jens; Werner, Thomas (Synlett)
Keywords: Organic Chemistry

The Formal Execution Semantics of SpecC - Müller, Wolfgang; Dömer, Rainer; Gerstlauer, Andreas (Proceedings of the ISSS02)
We present a rigorous but transparent semantics definition of the SpecC language that covers the execution of SpecC behaviors and their interaction with the kernel process. The semantics include wait, wait for, par, and try statements as they are introduced in SpecC. We present our definition in form of distributed abstract state machine (ASM) rules strictly following the lines of the SpecC Language Reference Manual. We mainly see our formal semantics in three application areas. First, it is a concise, unambiguous description for documentation and standardization. Second, it applies as a high-level, pseudo code-oriented specification for the implementation of a SpecC simulator. Finally, it is a first step for SpecC synthesis in order to identify similar concepts with other languages like VHDL and SystemC for the definition of common patterns and language subsets.
Keywords: Standardization; Kernel; Permission; Formal verification; Logic functions; Documentation; Reasoning about programs; Specification languages; Formal specifications; Software systems

Comparing Transcoding Tools for Use with a Generic User Interface Format - Plomp, Johan; Schäfer, Robbie; Müller, Wolfgang (Proceedings of the Extreme Markup Languages 2002)
This paper compares the use of three different approaches to transcoding of XML [Extensible Markup Language]-based user interface descriptions to other target formats. The source is the interface section of the XML-based markup language for user interfaces, UIML [User Interface Markup Language], which has been extended with a vocabulary for the description of generic user interfaces. Target formats used as examples for the comparison are HTML [Hypertext Markup Language], and VoiceXML. The compared means for transcoding are XSLT [Extensible Stylesheet Language Transformation], the UIML peers section with enhancements for transcoding, and RDL/TT [Rule Description Language for Tree Transformation], a Java-like transcoding language. Rendered by www.RenderX.com Comparing Transcoding Tools for Use with a Generic User Interface Format.

Specification of Real-Time Properties for UML Models - Flake, Stephan; Müller, Wolfgang (Proceedings of HICSS-35)
The Unified Modeling Language (UML) has received wide acceptance as a standard language in the field of software specification by means of different diagram types. In a recent version of UML, the textual Object Constraint Language (OCL) was introduced to support specification of constraints for UML models. But OCL currently does not provide sufficient means to specify constraints over the dynamic behavior of a model. This article presents an OCL extension that is consistent with current OCL and enables modelers to specify state-related time-bounded constraints. We consider the case study of a flexible manufacturing system and identify typical real-time constraints. The constraints are presented in our temporal OCL extension as well as in temporal logic formulae. For general application, we define a semantics of our OCL extension by means of a time-bounded temporal logic based on Computational Tree Logic (CTL).
Keywords: Unified modeling language; Logic; Formal verification; Real time systems; Programming profession; Vehicle dynamics; Software standards; Flexible manufacturing systems; Electronics industry; Protocols

Temporale Erweiterungen der OCL - Überblick und Aussichten - Flake, Stephan; Müller, Wolfgang
Die Object Constraint Language (OCL) wurde entwickelt, um Modelleinschränkungen beim objektorientierten Softwareentwurf mit der UML [14] ausdrücken zu können. Sie wird hauptsächlich benutzt, um Invarianten für Objekte sowie Vor-und Nachbedingungen von Operationen zu spezifizieren. Zurzeit bieten OCL und Echtzeiterweiterungen der UML nur bedingt geeignete Mittel, um temporale zeitbehaftete Modelleigenschaften zu beschreiben. Insbesondere kann man mit OCL keine Einschränkunge uber das dynamische Verhalten eines UML-Modells formulieren, die die Reihenfolge von Objektzuständen und Zustandsübergängen betreffen. Um ein korrektes Systemverhalten zu garantieren, ist es jedoch insbesondere bei zeitkritischen Anwendungen notwendig, solche zustandsbasierten zeitbehafteten Einschränkungen in einer formalen Art und Weise ausdrücken zu können. Es sind daher verschiedene Vorschläge veröffentlicht worden, in denen die OCL erweitert worden ist, um Modellierern die Möglichkeit zu geben, temporale Einschränkungen zu formulieren. Dieser Artikel gibt eine Überblick über die zurzeit bekannten Vorschläge und zeigt Ansätze für weitere Entwicklungen in diesem Bereich auf.

Liquid Crystal / Polymer Composites: From Polymer-Dispersed Liquid Crystals to Tunable Photonic Crystals - Kitzerow, Heinz-Siegfried; Hoischen, A.; Merstens, G.; Paelke, L.; Röder, T.; Stich, N.; Strauß, J.

Linear detection of optical polarization mode dispersion by arrival time modulation - Mirvoda, V; Sandel, D; Wust, F; Hinz, S; Noé, Reinhold (ELECTRICAL ENGINEERING)

Meditationen, Geheimnisse, Zufälle: Messiaens Konzept der langage communicable - Grotjahn, Rebecca (Frankfurter Zeitschrift für Musikwissenschaft)
Keywords: General Medicine

Einleitung - Grotjahn, Rebecca; Hoffmann, Freia (Geschlechterpolaritäten in der Musikgeschichte des 18. bis 20. Jahrhunderts)

Geschlechterpolaritäten in der Musikgeschichte des 18. bis 20. Jahrhunderts

Diva, Hure, Nachtigall: Sängerinnen im 19. Jahrhundert - Grotjahn, Rebecca (Hochschule für Musik Köln: Frauen in der Musikgeschichte. Dokumentation der Ringvorlesung im Sommersemester 2001)

Die ökonomischen Auswirkungen der Änderungen der steuerlichen Abschreibungsmodalitäten - König, Rolf; Sureth-Sloane, Caren (Die Betriebswirtschaft)

Partially Irreversible Investment Decisions and Taxation under Uncertainty: A Real Option Approach - Sureth-Sloane, Caren (German Economic Review)

Phonons in Confinement and the Boson Peak Using Nuclear Inelastic Absorption - Asthalter, T.; Bauer, Matthias; van Buerck, U.; Sergueev, I.; Franz, H.; Chumakov, A. I. (Hyperfine Interactions)
We have applied nuclear inelastic absorption (NIA) to the molecular glass former dibutylphthalate/ferrocene, both in bulk and in nanoporous matrices having pore sizes of 50 and 25 A, respectively. The quantity g(E)/E2, where g(E) is the vibrational phonon density of states (VDOS) of the resonant nuclei, exhibits a pronounced maximum at low energies. Confinement in pores leads to a suppression of the VDOS below 1.5 meV, independent of the pore size. Also in the scaled heat capacity C(T)/T3, we observe a decrease of the peak maximum for low temperatures. Our observations are discussed in the light of experimental and theoretical results on nanocrystals and a recent theoretical model for the boson peak.

Asymptotic Analysis for the Dunkl Kernel - Rösler, Margit; de Jeu, Marcel (Journal of Approximation Theory)
Keywords: Applied Mathematics; General Mathematics; Numerical Analysis; Analysis

Die Entdeckung der Terra incognita – Benjamin Bilse und sein reisendes Orchester - Grotjahn, Rebecca (Mitteilungen der Benjamin Bilse Gesellschaft)

‚Musik als Wissenschaft und Kunst‘ – Das Leipziger Konservatorium als Modell einer höheren musikalischen Bildung - Grotjahn, Rebecca (Musik, Wissenschaft und ihre Vermittlung. Bericht über die internationale Musikwissenschaftliche Tagung Hannover 2001)

Zur Bedeutung der Sinfonie im Musikleben 1850 bis 1875 - Grotjahn, Rebecca (Aspekte historischer und systematischer Musikforschung. Zur Symphonie im 19. Jahrhundert, zu Fragen der Musiktheorie, der Wahrnehmung von Musik und Anderes)

Reducing interference in stochastic time-frequency analysis without losing information - Schreier, Peter J.; Scharf, Louis L. (Proc. 36th\ Asilomar Conf.\ Signals Syst.\ Computers)
The analytic signal is commonly used in stochastic time-frequency analysis in Cohen’s class to reduce interference terms. However, we show that the usual time-frequency representation (TFR) based on the analytic signal gives only an incomplete signal description. This is because the analytic signal constructed from a non-stationary real signal is in general improper, which means that it has non-zero complementary correlation. We show how to augment the standard TFR by a complementary TFR to obtain a complete second-order characterization of the signal while still reducing interference terms compared to the TFR of the real signal.

Canonical coordinates for reduced-rank estimation of improper complex random vectors - Schreier, Peter J.; Scharf, Louis L. (Proc.\ IEEE Int.\ Conf.\ Acoustics, Speech and Signal Process.)
We consider the problem of minimum mean squared error (MMSE) estimation of complex random vectors in the improper case. Accounting for the information present in the complementary covariance requires the use of widely linear transformations. Based on these, we present the eigenanalysis of improper complex random vectors. This paves the way for a study of two different rank-reduced implementations of the complex Wiener Filter that make use of canonical coordinates: one that is optimum with respect to maximizing mutual information and one that minimizes mean squared error.

Quantum Key Distribution with Bright Entangled Beams - Silberhorn, Ch.; Korolkova, N.; Leuchs, G. (Physical Review Letters)
Keywords: General Physics and Astronomy

Evaluating Integrated Speech- and Image Understanding - Bauckhage, Christian; Fritsch, Jannik; Rohlfing, Katharina; Wachsmuth, Sven; Sagerer, Gerhard (Proc. IEEE International Conference on Multimodal Interfaces (ICMI’02))
The capability to coordinate and interrelate speech and vision is a virtual prerequisite for adaptive, cooperative, and flexible interaction among people. It is therefore to assume that human-machine interaction, too, would benefit from intelligent interfaces for integrated speech and image processing. In this paper, we first sketch an interactive system that integrates automatic speech processing with image understanding. Then, we concentrate on performance assessment which we believe is an emerging key issue in multimodal interaction. We explain the benefit of time scale analysis and usability studies and evaluate our system accordingly.

Evaluating Integrated Speech- and Image Understanding - Bauckhage, Christian; Fritsch, Jannik; Rohlfing, Katharina; Wachsmuth, Sven; Sagerer, Gerhard (Proc. IEEE International Conference on Multimodal Interfaces (ICMI’02))
The capability to coordinate and interrelate speech and vision is a virtual prerequisite for adaptive, cooperative, and flexible interaction among people. It is therefore to assume that human-machine interaction, too, would benefit from intelligent interfaces for integrated speech and image processing. In this paper, we first sketch an interactive system that integrates automatic speech processing with image understanding. Then, we concentrate on performance assessment which we believe is an emerging key issue in multimodal interaction. We explain the benefit of time scale analysis and usability studies and evaluate our system accordingly.

Gender and Translocal Networking through Information Technology - Spiegel, Anna; Nadine, Harig

Public Spheres, Public Islam, and Modernities - Spiegel, Anna

Collapse of sodium polyacrylate chains in calcium salt solutions - Schweins, R.; Huber, Klaus (The European Physical Journal E)
Keywords: Surfaces and Interfaces; General Materials Science; General Chemistry; Biophysics; Biotechnology

A comparative experimental study of the aggregation of Acid Red 266 in aqueous solution by use of 19F-NMR, UV/Vis spectroscopy and static light scattering - Neumann, Bernd; Huber, Klaus; Pollmann, Peter (Physical Chemistry Chemical Physics)
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Ca2+ and Cu2+ Induced Conformational Changes of Sodium Polymethacrylate in Dilute Aqueous Solution - Ikeda, Yuko; Beer, Michael; Schmidt, Manfred; Huber, Klaus (Macromolecules)
Keywords: Materials Chemistry; Inorganic Chemistry; Polymers and Plastics; Organic Chemistry

Model of Polydisperse Wormlike Stars and Its Application to Dyestuff Aggregates - Katzenstein, Armin; Huber, Klaus (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Shift of the photonic band gap in two photonic crystal/liquid crystal composites - Mertens, Guido; Röder, Thorsten; Schweins, Ralf; Huber, Klaus; Kitzerow, Heinz-Siegfried (Applied Physics Letters)
Keywords: Physics and Astronomy (miscellaneous)

Review of “Mediokratie. Die Kolonialisierung der Politik durch die Medien“ (Mediocracy: the colonization of polity by the media, by Thomas Mayer) - Fuchs, Christian (Das Argument 246)

Algorithms for function fields - Klüners, Jürgen (Experiment. Math.)
Let {\ASIE K}\,/{\small \ℚ}({\ASIE t \!}) be a finite extension. We describe algorithms for computing subfields and automorphisms of {\ASIE K}\,/{\small \ℚ}({\ASIE t }\!). As an application we give an algorithm for finding decompositions of rational functions in {\small \ℚ(α)}. We also present an algorithm which decides if an extension {\ASIE L}\,/{\small \ℚ}({\ASIE t \!}) is a subfield of {\ASIE K}. In case [{\ASIE K : \;}{\small\ℚ}({\ASIE t \!})] = [{\ASIE L : \;}{\small \ℚ}({\ASIE t \!})] we obtain a {\small \ℚ}({\ASIE t \!})-isomorphism test. Furthermore, we describe an algorithm which computes subfields of the normal closure of {\ASIE K}\,/{\small \ℚ}({\ASIE t \!}).
Keywords: algorithms; decompositions; Galois groups; subfields

Stufen zur Informationsgesellschaft. Festschrift zum 65. Geburtstag von Klaus Fuchs-Kittowski (Steps Towards the Information Society: Festschrift for Klaus Fuchs-Kittowski on the Occasion of his 65th Birthday)

Software Engineering and the Production of Surplus Value - Fuchs, Christian (Cultural Logic)